Indigenous Knowledge and Traditional Uses of Vangueria infausta subsp. infausta Burch in Northern KwaZulu-Natal, South Africa - Samukelisiwe Clerance Ngubane; Zoliswa Mbhele; Nontuthuko Rosemary Ntuli (Plants, 2025)
Indigenous top-priority fruit trees, like Vangueria infausta subsp. infausta. Burch (wild medlar), are essential for food security, climate resilience, and biodiversity. However, they remain underutilized due to limited documentation and integration into agricultural systems. This study presents the first ethnobotanical assessment of the wild medlar in Oyemeni, northeastern KwaZulu-Natal, South Africa. Surveys and interviews were conducted with 100 rural participants to explore its traditional uses, commercialization potential, and knowledge transmission. The findings reveal that the fruit is widely used in porridges, juices, and traditional beer, offering nutritional benefits such as vitamin C. Medicinally, it is valued for promoting oral health, wound healing, and spiritual protection. However, traditional knowledge is declining, particularly among the youth, due to generational shifts and modernization. The study highlights sustainable commercialization opportunities, such as value-added products and agroforestry integration, while emphasizing the need to preserve indigenous knowledge. These findings contribute to food security, biodiversity conservation, and cultural preservation in a changing socio-economic landscape. Future research should focus on biochemical evaluation of the plant’s medicinal properties and cross-regional comparisons.